Factors Related to Professional Pressure Among Thai Teachers Teaching Chinese at the Higher Education Level - Sanamad, Nidchakan; Numtong, Kanokporn (Journal of Ecohumanism, 2024)
This study investigates the correlation, obstacles, and opinions related to professional pressures among Thai teachers of Chinese in higher education. A sample of 108 teachers was selected using the accidental sampling method, and data were collected through a four-part questionnaire comprising: (1) General Information of the Respondents, (2) Factors Affecting Professional Pressure, (3) Obstacles and Opinions, and (4) Proposed Methods for Reducing Pressure. Data were analyzed using descriptive statistics and Pearson’s product-moment correlation. The findings indicate that the overall mean level of professional pressure is 3.41, with the mean values across six categories as follows: Job Descriptions (3.06), Roles and Duties (3.76), Interpersonal Relationships (2.78), Professional Advancement (3.57), Organizational Structures (3.61), and Course and Teaching Development (3.70). The correlational analysis revealed a significant positive relationship between professional pressures and quality of life, with notable correlations observed between Job Descriptions and Roles and Duties (r= .746, p <.001), Roles and Duties and Professional Advancement (r= .697, p < .001), and Professional Advancement and Organizational Structures (r= .658, p <.001). These results indicate interconnected relationships among the variables, suggesting that changes in one aspect of professional pressure may significantly influence others. All correlations are statistically significant, supporting the validity of these associations. Key stressors were heavy workloads, language demands, and cultural differences. Teachers with Chinese university backgrounds faced less pressure. The study highlights how these challenges affect teaching and offers recommendations to improve well-being.